Electrocatalytic reduction of carbon dioxide on gold–copper bimetallic nanoparticles: Effects of surface composition on selectivity. (1st October 2020) - Birhanu, Mulatu Kassie; Tsai, Meng-Che; Chen, Chun-Tse; Kahsay, Amaha Woldu; Zeleke, Tamene Simachew; Ibrahim, Kassa Belay; Huang, Chen-Jui; Liao, Yen-Fa; Su, Wei-Nien; Hwang, Bing Joe
Highlights: Bimetallic & monometallic NPs of Au & Cu are synthesized to catalyze CO2 reduction. Synergistic effect between Au & Cu in the alloy enhances the activity of the reduction. Supporting the NPs with MWCNT intensifies the activity & stability of the catalyst. Au-rich on the surface of electrocatalyst increases the selectivity towards CO. Correlate alloying extent & surface composition of bimetallic NPs with reaction intermediates. Abstract: In this work, bimetallic nanoparticles (NPs) of Au and Cu are synthesized for the electrochemical reduction reaction of CO2 (CO2 RR). It is known that the binding strength between the reduction intermediates and the electrocatalyst affects the selectivity of products, but how to correlate the performance with the surface composition, structure, and properties of a bimetallic electrocatalyst, instead of stoichiometric or bulk composition remains less discussed. AuCu and AuCu3 NPs with the size around ~8 nm were prepared. By excluding the size effect, the work studies the effects of surface composition and heteroatomic interaction on the selectivity and faradaic efficiency of the reduction products. Based on X-ray absorption spectroscopy (XAS), one can quantify the alloying extent and surface compositions of electrocatalysts, which are supposed to have the pivotal effects on the reaction pathways and the corresponding reduction products. It is found that high activity and notably improved CO selectivity of Au-Cu bimetallic NPs can be attributed to the heterometallic coordination and their electronic interactions. The reduction products were analyzed by gas chromatography and nuclear magnetic resonance (NMR) spectroscopy. Nearly 60 mA cm −2 of current density was recorded at -0.91 V vs. RHE, and selectivity of 78±4.3% CO was obtained using AuCu. Graphical abstract: Image, graphical abstract